Fusobacterium nucleatum in tumors: from tumorigenesis to tumor metastasis and tumor resistance - Chun Ye; Xiao Liu; Zilun Liu; Chuxuan Pan; Xiaowei Zhang; Zhanyi Zhao; Haitao Sun (Cancer Biology & Therapy)
Fusobacterium nucleatum, an anaerobic Gram-negative bacterium primarily residing in the oral cavity, has garnered significant attention for its emerging role in cancer progression and prognosis. While extensive research has revealed mechanistic links between Fusobacterium nucleatum and colorectal cancer, a comprehensive review spanning its presence and metastatic implications in cancers beyond colorectal origin is conspicuously absent. This paper broadens our perspective from colorectal cancer to various malignancies associated with Fusobacterium nucleatum, including oral, pancreatic, esophageal, breast, and gastric cancers. Our central focus is to unravel the mechanisms governing Fusobacterium nucleatum colonization, initiation, and promotion of metastasis across diverse cancer types. Additionally, we explore Fusobacterium nucleatum‘s adverse impacts on cancer therapies, particularly within the domains of immunotherapy and chemotherapy. Furthermore, this paper underscores the clinical research significance of Fusobacterium nucleatum as a potential tumor biomarker and therapeutic target, offering a novel outlook on its applicability in cancer detection and prognostic assessment.